Association between heavy metal exposure and asthma in adults: Data from the Korean National Health and Nutrition Examination Survey 2008–2013 - Mijung Jang; Dohhee Kim; Seunghee Lee; KyooSang Kim (PLoS ONE, 2025)
Risk factors for asthma include genetic, host, and environmental factors such as allergens, smoking, and exposure to chemicals. Heavy metals from air pollution or contaminated water and food can also trigger asthma. This study aimed to identify the biological exposure levels of blood lead, mercury, and cadmium, and determine the association of asthma with single and multiple exposures to these heavy metals using data from the Korean National Health and Nutrition Examination Survey (KNHANES) conducted between 2008 and 2013. A weighted analysis of 40,328 adults aged ≥ 20 years was conducted. Variables included blood heavy metal levels, health behaviors, demographic characteristics, and asthma status. Logistic regression was used to identify the association between the blood heavy metal levels and the odds ratio (OR) of asthma in adults. The overall asthma prevalence was 3.0%. The geometric mean values for blood lead, mercury, and cadmium were 2.14 μg/dL, 3.72 μg/L, and 0.96 μg/L, respectively. An association between asthma and high blood lead levels was observed, with the highest level group showing a statistically significant association. Blood mercury and cadmium were significantly associated with asthma in the highest quartile of blood levels. After adjusting for the demographic and health behavior variables, significant associations with asthma persisted for the highest quartiles of all heavy metals. Multiple exposures in the highest quartile also showed a significant association with asthma. This study demonstrated a significant association between blood heavy metal levels and asthma in adults, emphasizing the need to reduce exposure to lead, cadmium, and mercury as a preventive measure against asthma in adults.